2003
DOI: 10.1055/s-2003-39294
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Axially ChiralResorcinarenes from Resorcinol Monoalkyl Ethers and Aldehyde Dimethylacetals

Abstract: Novel racemic tetraalkoxyresorcinarene derivatives can be prepared in good yields by boron trifluoride diethyl etherate-catalysed reactions of 1,1-dimethoxyalkanes with resorcinol monoalkyl ethers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In this regard, we decided to use Lewis acid as a catalyst. The most suitable is boron trifluoride etherate, which is often used in the reactions of acetals with nucleophiles. Thus, refluxing acetal 4a with 4-bromoaniline and boron trifluoride etherate in toluene led to quinoline 10 (Scheme ). It is noteworthy that refluxing compound 9 in toluene in the presence of boron trifluoride etherate also resulted in the isolation of quinoline 10 in 81% yield.…”
Section: Resultsmentioning
confidence: 53%
“…In this regard, we decided to use Lewis acid as a catalyst. The most suitable is boron trifluoride etherate, which is often used in the reactions of acetals with nucleophiles. Thus, refluxing acetal 4a with 4-bromoaniline and boron trifluoride etherate in toluene led to quinoline 10 (Scheme ). It is noteworthy that refluxing compound 9 in toluene in the presence of boron trifluoride etherate also resulted in the isolation of quinoline 10 in 81% yield.…”
Section: Resultsmentioning
confidence: 53%
“…5 Resorcin [4]arenes can be synthesised using a straightforward one step procedure and it has been shown that the interaction of an ethanolic solution of a variety of aldehydes with resorcinol in the presence of protic acids results in the rapid formation of resorcin [4]arenes in high yields. [6][7][8][9][10][11][12][13] Racemic tetraalkoxyresorcinarenes can be prepared from a range of resorcinol-monoalkyl ethers in dichloromethane, using boron trifluoride-etherate as the catalyst. [11][12][13] Scheme 1 shows the synthetic route for the formation of racemic tetraalkoxyresorcinarenes, where the M and P designators refer to the two different forms of the cyclochiral macromolecule.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] Racemic tetraalkoxyresorcinarenes can be prepared from a range of resorcinol-monoalkyl ethers in dichloromethane, using boron trifluoride-etherate as the catalyst. [11][12][13] Scheme 1 shows the synthetic route for the formation of racemic tetraalkoxyresorcinarenes, where the M and P designators refer to the two different forms of the cyclochiral macromolecule. [14][15][16][17] The properties of the central cavity, such as appropriate cavity size, hydrophobicity and rigidity, depend on the substituents on both rims.…”
Section: Introductionmentioning
confidence: 99%